2019
DOI: 10.1007/s00192-019-04067-9
|View full text |Cite
|
Sign up to set email alerts
|

Childbirth after mid-urethral sling surgery: effects on long-term success and complications

Abstract: II 2 AIMS OF THE THESIS .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 135 publications
(221 reference statements)
0
3
0
Order By: Relevance
“…Several studies have shown good long-term efficacy rates after MUS operations [19], but they have not reported post-operative hysterectomies. As a secondary result, one study showed a twice higher rate of symptomatic SUI after MUS in women with a subsequent hysterectomy [20]. However, only eight women with a subsequent…”
Section: Discussionmentioning
confidence: 96%
“…Several studies have shown good long-term efficacy rates after MUS operations [19], but they have not reported post-operative hysterectomies. As a secondary result, one study showed a twice higher rate of symptomatic SUI after MUS in women with a subsequent hysterectomy [20]. However, only eight women with a subsequent…”
Section: Discussionmentioning
confidence: 96%
“…In 2019, one year after our study was published, Dyrkorn et al published a Norwegian study very similar to ours, which allows for interesting comparisons. 166 Their study included 72 women (39 vaginal deliveries, 33 cesarean sections) with and 156 without childbirth after a MUS procedure. The median follow-up time was 10 years after the initial MUS procedure, as compared to 9 years in our study.…”
Section: Study IIImentioning
confidence: 99%
“…Studies have documented good continence outcomes in women who deliver following MUS, and many of these women also experienced satisfactory continence throughout pregnancy. [113][114][115][116] Similarly, one retrospective study on patients with a previous pubovaginal sling demonstrated unchanged incontinence in eight out of nine women post-delivery. 117 Rare complications, such as urinary retention, may occur, with one case study documenting the need for mesh transection during pregnancy due to refractory urinary retention.…”
Section: How Should a Young Woman Who Desires To Have Children In The...mentioning
confidence: 96%